PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA DI PENGADILAN NEGERI MERAUKE - Emiliana Bernadina Rahail (SOCIETAS, 2014)
This study aims to determine (1) the judge's action in completing the crime of child in Merauke District Court (2) determine the implementation of the provision of legal protection against criminal as a child in proceedings in the District Court of Merauke.This study was carried out in their in Merauke Merauke, especially in the District Court. The method used in this is the use of primary data and secondary data, the data obtained in this study qualitatively managed. The results showed that the implementation of the trial in a criminal case settlement is done by children in Merauke District Court in the case of criminal offenses of murder, fighting in public, assault, theft and promiscuity, most (86%) were completed through the criminal justice system. And in the case of the crime of theft and gambling fraction (14%) were completed outside of the criminal justice process by using diversion.The process of implementation of the trial to the protection of children's rights as a criminal in Merauke District Court trial done at the beginning and until there is a final decision that the proceedings concerning the granting of legal protection of the rights of children as criminals are still not fully run optimally, because as a child criminals do not want to use his rights as a child in the legal protection